CULTIVATION AND PROTECTION OF SEASONAL FLOWERS IN GREENHOUSES IN STRUMICA (Journal of Agriculture and Plant Sciences, 2019)
In the period 2014 and 2015 different varieties and hybrids of seasonal flowers were examined in conditions of greenhouses in Strumica.In the two years studied, there were 9 flowering varieties: Verbena (Verbena officinalis L.); Salvia (Salvia officinalis L.); Aliciaum (Alyssum martimum Lam. Synonym Lobulariamaritima); Petunia (Petunia sp.); Begonia (Begonia sp.); Tagetes (Tagetes sp.); Portulaca (Portulaca grandiflora); Impatiens (Impatiens sp.) and Lobelia L.The production technique and technology were examined in conditions of production, then the conditions of seed production, seedling production, planting and care during the whole vegetation were studied (spraying, nourishing and preventive protection against diseases and pests.Namely, all examined variants in comparison with the control variant (untreated) are characterized by higher yield, quality and earlier arrive for placing on the market.Five fungicides were used for preventative care: Ridomil Gold MZ 68 WG, Score 250 EC, Switch 62.5 WG, Bravo 500 SC and Topas 100 EC and five different insecticides: Actara 25 WG, Confidor SL 200, Karate Zeon 5 CS, Chess 50 WG and Pirimor 50 WG. Of all the tested fungicides and insecticides for examination, five variants, consisting of two fungicides and one insecticide, were prepared (used). All examined variants yielded a high percentage of efficiency.The best performance in 2014 was achieved with a variant (Bravo 500 SC, Topas 100 EC and Chess 50 WG) and (Topas 100 EC, Switch 62.5 WG and Pirimor 50 WG), with a coefficient of efficiency of 99.6%.The index of disease in 2014 in the control variant was 48.2%.In 2015, the control index variation was 54.1%, and the highest biological efficiency was achieved with the variant (Bravo 500 SC, Topas 100 EC and Chess 50 WG), with a coefficient of efficiency of 98.4%. In addition to our experiments, our examination was supplemented by surveys.From the polls it was found that the development of flower growing in greenhouses in ourspaces is at an initial stage and requires appropriate resources, commitment and time, and that it is still at family business. It also requires the state to develop a strategy for the development of floriculture and to invest financially funds, which will also contribute to the development of the national economy. Key words: flowers, fungicides, insecticides, surveys, protection